Despatologization of Transexuaility (Revista Iberoamericana de Bioética, 2019)
This work aims to present the need for transsexuality to cease to be a pathology, making the importance of this despatologization visible and currently the placement of the term transsexualism contributes to the development of prejudices and other problems. It is important to define some used and confused terms such as gender, sexual orientation and gender identity, highlighting their distinctions and where each one fits. Despite several studies, transsexualism is classified as a psychological disorder, listed as a sexual identity disorder, and redesignation, although broad, is the treatment used in the sexual surgical issue that is sufficient to satisfy the transsexual.
Keywords: transsexual; biolaw; despatologization